Association between change in self-efficacy to resist drinking and drinking behaviors among an HIV-infected sample: Results from a large randomized controlled trial. (May 2018) - Gause, Nicole K; Elliott, Jennifer C; Delker, Erin; Stohl, Malka; Hasin, Deborah; Aharonovich, Efrat
Heavy drinking among HIV-infected individuals is associated with health complications. Health-behavior self-efficacy may be characteristically low among this population or negatively affected by HIV-infected status. We assessed whether self-efficacy to resist drinking increased during brief educational and motivational drinking-reduction interventions within HIV primary care and whether increases in self-efficacy predicted drinking among HIV-infected heavy drinkers. Results indicate that increases in self-efficacy from baseline to end-of-intervention inversely predicted drinking at end-of-intervention and at follow-up. Findings suggest that brief treatment interventions within HIV primary care may promote self-efficacy and that increases in self-efficacy predict initiation and maintenance of drinking reductions among HIV patients.